The impact of life stressors on depression in college students: the chain mediating role of environmental adaptation and coping styles - Huanhuan Yang; Jing Zhao; Yuan Qin; Yongning Qian (Frontiers in Psychology, 2025)
ObjectiveTo explore the chain mediating role of environmental adaptation and coping styles between life stressors and depression among university students.MethodsTwelve thousand, one hundred ninety-eight college students were investigated with Student Life Stress Inventory (SLSI), Depressive Episode Scale (DES), Environmental Adaptation Scale (EAS), and Coping Style Scale (CSS). The chain intermediary model was constructed and verified with SPSS.ResultsLife stressors and coping styles were positive predictors of depression, while environmental adaptation was a negative predictors. The direct impact of life stressors on depression was significant. Environmental adaptation and coping styles exhibited both independent mediating effects and a chain mediating effect.ConclusionLife stressors can directly lead to depression, and indirectly exacerbate depression through environmental adaptation and coping styles. Therefore, reducing burden, enhancing environmental adaptability and learning appropriate coping strategies can effectively prevent depression.